Antena Mikrostrip Triple-Band untuk Aplikasi LTE dan L-Band Radar - Hilyawan, Mohamad Reynaldy; Alam, Syah; Surjati, Indra (Yayasan Petra Harapan Bangsa, 2023)
In this research, microstrip antenna design is carried out using the inset and slot methods. This research proposes a microstrip antenna with three working frequencies, namely 1.3 GHz for radar applications and 1.8 and 2.6 GHz for 4G LTE applications. To fulfill the proposal, the type of substrate used is FR4 with a value of 4.3 for ɛr and 1.6 millimeters for h. This research resulted in the initial design of a dual-band microstrip antenna that works at frequencies of 1.8 and 2.6 GHz for 4G LTE applications. Furthermore, the proposed T-slot and U-slot methods are added to generate a resonant frequency at 1.3 GHz for radar applications. The return loss results in the inset method are -20.76 dB at 1.79 GHz and -20.20 dB at 2.60 GHz. The addition of T-slot with fixed inset parameters results in -11.66 dB at 1.37 GHz, -17.31 dB at 1.95 GHz, and -20.56 dB at 2.59 GHz, then the addition of inverted U-slot results in -33.49 dB at 1.30 GHz, -22.13 dB at 1.80 GHz and -21.36 dB at 2.59 GHz. The simulation results obtained bandwidth of the working frequency at the third iteration are 1.04%, 2.22% and 1.18%. This research is simulated and designed with Simulator software. This research can be recommended as a radar and LTE communication system.